Morphology-selected synthesis of copper ferrite via spray drying with excellent sodium storage properties. Issue 16 (November 2019) - Yan, Huaicong; Zhang, Yiyong; Wang, Yunxiao; Liu, Jiaming; Li, Xue; Zhang, Yingjie; Dong, Peng
Abstract: A series of morphology-selected copper ferrite (CuFe2 O4 ) anode materials for sodium ion batteries were firstly prepared via a highly efficient spray drying method using glycine as the complex and accelerator. It was found that the glycine/nitrate (G/N) molar ratio has an important influence on the crystallinity, morphology and electrochemical properties of sodium storage. Compared with the other prepared materials, the G/N-0.3 (glycine-nitrate molar ratio of 0.3) exhibits the most excellent electrochemical performance. The excellent electrochemical properties can be attributed to the optimized molar ratio of glycine-nitrate, which induce a good crystallinity with a proper porous structure, thereby improving the cycle life of the battery.